Autoimmune encephalitis associated with an ovarian teratoma in a 29-year old woman - Plaikner, A; Jacob, A; Rother, J; Kohler, C (Clinical Journal of Obstetrics and Gynecology, 2019)
NMDA receptor encephalitis is a rare disease first described in 2007. Anti-NMDA receptor encephalitis affects mostly young women as neoplasms, mostly ovarian teratomas, are the underlying cause. The disease is caused by antibodies binding to extracellular epitopes of neuronal cell-surface, which leads to an internalization of NMDA-receptors. The characteristic syndrome of patients with anti-NMDAR as well as its recovery follows a certain pattern. Treatment includes immunotherapy and removal of the immunologic trigger. This case report describes a young woman with anti-NMDA receptor encephalitis caused by an ovarian teratoma.